2014
DOI: 10.1002/mrm.25521
|View full text |Cite
|
Sign up to set email alerts
|

A method for safety testing of radiofrequency/microwave‐emitting devices using MRI

Abstract: Purpose Strict regulations are imposed on the amount of radiofrequency (RF) energy that devices can emit to prevent excessive deposition of RF energy into the body. In this study, we investigated the application of MR temperature mapping and 10-g average specific absorption rate (SAR) computation for safety evaluation of RF-emitting devices. Methods Quantification of the RF power deposition was shown for an MRI-compatible dipole antenna and a non–MRI-compatible mobile phone via phantom temperature change mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 21 publications
1
16
0
Order By: Relevance
“…Gaussian noise with 0 mean and standard deviation of 0.035 °C was injected into temperature difference maps. Noise was chosen based on empirical noise figures in MR thermal mapping phantom data in MRI literature [Alon et al, 2015]. HEI reconstruction framework used simulated temperature maps to reconstruct SAR using different lambda values between 0 and 80 in a logarithmic scale.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gaussian noise with 0 mean and standard deviation of 0.035 °C was injected into temperature difference maps. Noise was chosen based on empirical noise figures in MR thermal mapping phantom data in MRI literature [Alon et al, 2015]. HEI reconstruction framework used simulated temperature maps to reconstruct SAR using different lambda values between 0 and 80 in a logarithmic scale.…”
Section: Methodsmentioning
confidence: 99%
“…Gultekin and Moeller [2013] have shown that magnetic resonance (MR) methods can be used to measure temperature increase due to RF energy absorption, where the magnitude of temperature increase was a function of RF power and exposure time in brain equivalent gels and brain tissue [Gultekin and Moeller, 2013]. Recently, high-resolution MR thermal mapping has been utilized for assessment of RF energy absorption from handheld wireless devices [Alon et al, 2015] that output less than 1W of power.…”
Section: Introductionmentioning
confidence: 99%
“…E-field probe-based systems [7], electro-optical (EO) probe-based systems [8], and optical fiber thermal sensor-based systems [9] are classified as invasive measurement systems. Infrared (IR) measurement systems [10], thermal scanner systems [11], power density (PD) measurements [12], and optical SAR systems [13], [14] can be classified as noninvasive measurement systems with minimal to no interactions between the device under test (DUT) and the measurement system.…”
Section: Measurement Systemsmentioning
confidence: 99%
“…Recently, the technique has been expanded to accommodate high-frequency wireless device sources that have traditionally been considered to be incompatible with MRI [11]. The method is sensitive to small temperature changes (<0.1°C) and evaluates SAR with millimeter resolution [11]. Recent studies have shown that from the 3-D temperature change, SAR can be computed via direct inversion of the heat equation [26].…”
Section: Measurement Systemsmentioning
confidence: 99%
“…MRI temperature mapping and understanding of RF heating while using MRI scanners for MRI compatible devices was given by [13,14]. MRI temperature mapping to characterize heating from wireless devices that are not necessarily MRI compatible and calculation of 10 g average SAR using the heat mappings has been suggested by [15]. Accurate calculation of SAR using magnetic resonance temperature images and measured thermal properties of the phantom have been done by [16].…”
Section: Introductionmentioning
confidence: 99%